14. [tex]\lim_{x\rightarrow a}\frac{x^2-(a+b)x+ab}{x-a}=\lim_{x\rightarrow a}\frac{(x-a)(x-b)}{x-a}=\lim_{x\rightarrow a}x-b=a-b[/tex]
15. [tex]\lim_{x\rightarrow 0}\frac{\sqrt{ax+9}-3}{ax^2+bx}=\lim_{x\rightarrow 0}\frac{ax}{(ax^2+bx)(\sqrt{ax+9}+3)}=\lim_{x\rightarrow 0}\frac{a}{(ax+b)(\sqrt{ax+9}+3)}=\frac{a}{6b}[/tex]
16. [tex]\lim_{x\rightarrow -\infty}(\sqrt{x^2+ax+5}+x)=\lim_{x\rightarrow -\infty}\frac{ax+5}{\sqrt{x^2+ax+5}-x}=\lim_{x\rightarrow -\infty}\frac{a+\frac{5}{x}}{-\sqrt{1+\frac{a}{x}+\frac{5}{x^2}}-1}=-\frac{a}{2}[/tex]
Từ đó [TEX]a=-10[/TEX]
17. [tex]\lim_{x\rightarrow a}\frac{x^4-a^4}{x-a}=\lim_{x\rightarrow a}(x^3+x^2a+xa^2+a^3)=4a^3[/tex]